Development, construction, and evaluation of an alternative dosimetry phantom for computed tomography - Lukmanda Evan Lubis; Windi Dliya Najmah; Yuni Muliyanti; Ika Hariyati; Dea Ryangga; Terry Mart; Hilde Bosmans; Djarwani Soeharso Soejoko (Journal of Medical Physics, 2023)
This article aims to present the development, construction, and evaluation of an alternative computed tomography dose index (CTDI) phantom. Epoxy resin was mixed with an iodine-based contrast agent to produce radiological characteristics resembling polymethyl methacrylate (PMMA) as a standard CTDI phantom. As a preliminary study, testing was carried out using computed tomography images (80 and 120 kVp) on 12 variations of epoxy-iodine resin mixtures to obtain relative electron density (ρe) values and effective atomic numbers (Zeff) of the samples. The alternative CTDI phantoms were then constructed with a resin-iodine mixture using iodine concentrations that yield on closest ρe and Zeff values to those of PMMA. The evaluation was carried out by comparing dose measurement results at various energies between the alternative phantom and the International Electrotechnical Commission-standard CTDI phantom. At a concentration of 0.46%, the epoxy resin has ρe and Zeff with a deviation against PMMA of 0.12% and 1.58%, respectively, so that composition was chosen for the alternative CTDI phantom construction. The average dose discrepancy values were 5% and 1%, respectively, for the head and body phantoms in the tested tube voltages of 80 kVp, 100 kVp, 120 kVp, and 135 kVp. The Student's t-test result between the alternative and the standard phantoms also showed P < 0.05, indicating the comparability of the alternative CTDI phantom with the standard CTDI phantom.